Synthesis of (+)-obtusenyne. - Mak, S; Curtis, N; Payne, A; Congreve, MS; Wildsmith, A; Francis, C; Davies, J; Pascu, S; Burton, J; Holmes, AB (2008)
An enantioselective synthesis of the halogenated medium-ring ether natural product (+)-obtusenyne is reported which uses the ring expansion of a seven-membered ketene acetal by means of a Claisen rearrangement to construct the core nine-membered oxygen heterocycle. The trans substituents across the ether linkage were established by using a transition-metal-catalyzed intramolecular hydrosilation reaction of an exo-cyclic enol ether. In addition, a formal synthesis of ent-obtusenyne from 2-deoxy-D-ribose is reported. A number of interesting points regarding the chemistry of medium-ring oxygen heterocycles are highlighted.